2014
DOI: 10.1089/zeb.2014.0989
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Analysis of Behavior in Zebrafish Larvae: Effects of Feeding

Abstract: Early brain development can be influenced by numerous genetic and environmental factors, with long-lasting effects on brain function and behavior. Identification of these factors is facilitated by high-throughput analyses of behavior in zebrafish larvae, which can be imaged in multiwell or multilane plates. However, the nutritional needs of zebrafish larvae during the behavioral experiments are not fully understood. Zebrafish larvae begin feeding between 4 and 5 days postfertilization (dpf), but can live solel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 32 publications
(53 reference statements)
2
48
0
Order By: Relevance
“…Starvation increases the responsiveness of several fish species to prey, but actually suppresses escape from predatory threats, possibly reflecting elevated risk-tolerance during food-search behavior (Ware, 1972; Croy and Hughes, 1991; Munk, 1995). Intriguingly, similar results have already been obtained in zebrafish larvae: unfed larvae show reduced avoidance of a simulated visual threat (Clift et al, 2014). Experiments in zebrafish confirm that changes in sensory responsiveness can be highly modality specific.…”
Section: Introductionsupporting
confidence: 82%
“…Starvation increases the responsiveness of several fish species to prey, but actually suppresses escape from predatory threats, possibly reflecting elevated risk-tolerance during food-search behavior (Ware, 1972; Croy and Hughes, 1991; Munk, 1995). Intriguingly, similar results have already been obtained in zebrafish larvae: unfed larvae show reduced avoidance of a simulated visual threat (Clift et al, 2014). Experiments in zebrafish confirm that changes in sensory responsiveness can be highly modality specific.…”
Section: Introductionsupporting
confidence: 82%
“…During the first 15 minutes, behaviors are analyzed without visual stimuli. During the subsequent 15 minutes, behaviors are analyzed in the presence of an aversive visual stimulus, a red moving bar, which the larvae avoid [21, 25]. We found that day 3 cyclosporine exposures affected the avoidance response (Fig 7A), swim speed (Fig 7B), resting (Fig 7C), the average distance between larvae (Fig 7D), the percentage of time that larvae are close together (Fig 7E), and the percentage of time the larvae spend on the edge of the swimming area (Fig 7F).…”
Section: Resultsmentioning
confidence: 99%
“…The 5 dpf larvae receive nutrients from their yolk sac and effects of feeding can be avoided at this time [21]. The larvae were imaged with a custom-built imaging system, as described previously [24-25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larvae were exposed during different days of development and then analyzed for behavior at 5 days post fertilization (dpf), a timepoint chosen because larval activity does not change at this age with external feeding (Clift et al, 2014). Concurrent time points were used in order to analyze AChE activity using the Ellman assay (Ellman et al, 1961).…”
Section: Introductionmentioning
confidence: 99%